All Days 2011
DOI: 10.2118/141419-ms
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Wettability Alteration with Changes in Eelative Permeability of Gas Condensate Reservoirs

Abstract: In gas condensate reservoirs, considerable productivity loss occurs after the pressure near the production wells drops below the dew point of the hydrocarbon fluids. Over the years, several methods have been proposed to restore gas production rates after a decline in well productivity owing to condensate and/or water blocking. These methods such as gas recycling, hydraulic fracturing and solvent injection have shown to restore the production on a temporary basis only. Altering the wettability of reservoir rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Normal decane spontaneous imbibition before and after treating the core sample with 4% at high temperature, reprinted with permission from Alajmei, 2017. Copyright (2017, University of Oklahoma) …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Normal decane spontaneous imbibition before and after treating the core sample with 4% at high temperature, reprinted with permission from Alajmei, 2017. Copyright (2017, University of Oklahoma) …”
Section: Resultsmentioning
confidence: 99%
“…Relative permeability of the Berea sandstone before and after treatment with 4 and 8%, reprinted with permission from Alajmei, 2017. Copyright (2017, University of Oklahoma) …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bang et al [1] evaluated the effect of wettability alteration in a sandstone core at higher interfacial tension conditions (≈12 mN/m) and reached IFs between 3 and 4. Other authors reported IF in the range 1-2, for both sandstone and carbonate cores [61][62][63], but no details of the fluid properties were discussed.…”
Section: Improvement Factormentioning
confidence: 99%
“…Bang et al [86] evaluated the effect of wettability alteration in a sandstone core at higher interfacial tension conditions (≈ 12mN/m) and reached IFs between 3 and 4. Other authors reported IF in the range 1-2, for both sandstone and carbonate cores [99,100,101], but no details of the fluid properties were discussed.…”
Section: Improvement Factormentioning
confidence: 99%